Effects of climate warming on Sphagnum photosynthesis in peatlands depend on peat moisture and species‐specific anatomical traits - Vincent E. J. Jassey; Constant Signarbieux (Global Change Biology, 2019)
Climate change will influence plant photosynthesis by altering patterns of temperature and precipitation, including their variability and seasonality. Both effects may be important for peatlands as the carbon (C) sink potential of these ecosystems depends on the balance between plant C uptake through photosynthesis and microbial decomposition. Here, we show that the effect of climate warming on Sphagnum community photosynthesis toggles from positive to negative as the peatland goes from rainy to dry periods during summer. More particularly, we show that mechanisms of compensation among the dominant Sphagnum species ( Sphagnum fallax and Sphagnum medium ) stabilize the average photosynthesis and productivity of the Sphagnum community during summer despite rising temperatures and frequent droughts. While warming had a negligible effect on S. medium photosynthetic capacity ( A max ) during rainy periods, A max of S. fallax increased by 40%. On the opposite, warming exacerbated the negative effects of droughts on S. fallax with an even sharper decrease of its A max while S. medium A max remained unchanged. S. medium showed a remarkable resistance to droughts due to anatomical traits favouring its water holding capacity. Our results show that different phenotypic plasticity among dominant Sphagnum species allow the community to cope with rising temperatures and repeated droughts, maintaining similar photosynthesis and productivity over summer in warmed and control conditions. These results are important because they provide information on how soil water content may modulate the effects of climate warming on Sphagnum productivity in boreal peatlands. It further confirms the transitory nature of warming‐induced photosynthesis benefits in boreal systems and highlights the vulnerability of the ecosystem to excess warming and drying.

Plastic and genetic responses of a common sedge to warming have contrasting effects on carbon cycle processes - Tom W. N. Walker; Wolfram Weckwerth; Luca Bragazza; Lena Fragner; Brian G. Forde; Nicholas J. Ostle; Constant Signarbieux; Xiaoliang Sun; Susan E. Ward; Richard D. Bardgett (Ecology Letters, 2019)
Climate warming affects plant physiology through genetic adaptation and phenotypic plasticity, but little is known about how these mechanisms influence ecosystem processes. We used three elevation gradients and a reciprocal transplant experiment to show that temperature causes genetic change in the sedge Eriophorum vaginatum . We demonstrate that plants originating from warmer climate produce fewer secondary compounds, grow faster and accelerate carbon dioxide ( CO 2 ) release to the atmosphere. However, warmer climate also caused plasticity in E. vaginatum , inhibiting nitrogen metabolism, photosynthesis and growth and slowing CO 2 release into the atmosphere. Genetic differentiation and plasticity in E. vaginatum thus had opposing effects on CO 2 fluxes, suggesting that warming over many generations may buffer, or reverse, the short‐term influence of this species over carbon cycle processes. Our findings demonstrate the capacity for plant evolution to impact ecosystem processes, and reveal a further mechanism through which plants will shape ecosystem responses to climate change.

Vapor–pressure deficit and extreme climatic variables limit tree growth - Paula Sanginés de Cárcer; Yann Vitasse; Josep Peñuelas; Vincent E. J. Jassey; Alexandre Buttler; Constant Signarbieux (Global Change Biology, 2018)
Assessing the effect of global warming on forest growth requires a better understanding of species‐specific responses to climate change conditions. Norway spruce and European beech are among the dominant tree species in Europe and are largely used by the timber industry. Their sensitivity to changes in climate and extreme climatic events, however, endangers their future sustainability. Identifying the key climatic factors limiting their growth and survival is therefore crucial for assessing the responses of these two species to ongoing climate change. We studied the vulnerability of beech and spruce to warmer and drier conditions by transplanting saplings from the top to the bottom of an elevational gradient in the Jura Mountains in Switzerland. We (1) demonstrated that a longer growing season due to warming could not fully account for the positive growth responses, and the positive effect on sapling productivity was species‐dependent, (2) demonstrated that the contrasting growth responses of beech and spruce were mainly due to different sensitivities to elevated vapor–pressure deficits ( VPD ), (3) determined the species‐specific limits to VPD above which growth rate began to decline, and (4) demonstrated that models incorporating extreme climatic events could account for the response of growth to warming better than models using only average values. These results support that the sustainability of forest trees in the coming decades will depend on how extreme climatic events will change, irrespective of the overall warming trend.

Asymmetric effects of cooler and warmer winters on beech phenology last beyond spring - Constant Signarbieux; Ester Toledano; Paula Sanginés de Carcer; Yongshuo H. Fu; Rodolphe Schlaepfer; Alexandre Buttler; Yann Vitasse (Global Change Biology, 2017)
In temperate trees, the timings of plant growth onset and cessation affect biogeochemical cycles, water, and energy balance. Currently, phenological studies largely focus on specific phenophases and on their responses to warming. How differently spring phenology responds to the warming and cooling, and affects the subsequent phases, has not been yet investigated in trees. Here, we exposed saplings of Fagus sylvatica L. to warmer and cooler climate during the winter 2013–2014 by conducting a reciprocal transplant experiment between two elevations (1,340 vs. 371 m a.s.l., ca. 6°C difference) in the Swiss Jura mountains. To test the legacy effects of earlier or later budburst on the budset timing, saplings were moved back to their original elevation shortly after the occurrence of budburst in spring 2014. One degree decrease in air temperature in winter/spring resulted in a delay of 10.9 days in budburst dates, whereas one degree of warming advanced the date by 8.8 days. Interestingly, we also found an asymmetric effect of the warmer winter vs. cooler winter on the budset timing in late summer. Budset of saplings that experienced a cooler winter was delayed by 31 days compared to the control, whereas it was delayed by only 10 days in saplings that experienced a warmer winter. Budburst timing in 2015 was not significantly impacted by the artificial advance or delay of the budburst timing in 2014, indicating that the legacy effects of the different phenophases might be reset during each winter. Adapting phenological models to the whole annual phenological cycle, and considering the different response to cooling and warming, would improve predictions of tree phenology under future climate warming conditions.

Response to Editor to the comment by Delarue (2016) to our paper entitled ‘Persistent high temperature and low precipitation reduce peat carbon accumulation’ - Luca Bragazza; Alexandre Buttler; Bjorn J. M. Robroek; Remy Albrecht; Claudio Zaccone; Vincent E. J. Jassey; Constant Signarbieux (Global Change Biology, 2017)

Persistent high temperature and low precipitation reduce peat carbon accumulation - Luca Bragazza; Alexandre Buttler; Bjorn J.M. Robroek; Remy Albrecht; Claudio Zaccone; Vincent E.J. Jassey; Constant Signarbieux (Global Change Biology, 2016)
Extreme climate events are predicted to become more frequent and intense. Their ecological impacts, particularly on carbon cycling, can differ in relation to ecosystem sensitivity. Peatlands, being characterized by peat accumulation under waterlogged conditions, can be particularly sensitive to climate extremes if the climate event increases soil oxygenation. However, a mechanistic understanding of peatland responses to persistent climate extremes is still lacking, particularly in terms of aboveground–belowground feedback. Here, we present the results of a transplantation experiment of peat mesocosms from high to low altitude in order to simulate, during 3 years, a mean annual temperature c. 5 °C higher and a mean annual precipitation c. 60% lower. Specifically, we aim at understanding the intensity of changes for a set of biogeochemical processes and their feedback on carbon accumulation. In the transplanted mesocosms, plant productivity showed a species‐specific response depending on plant growth forms, with a significant decrease (c. 60%) in peat moss productivity. Soil respiration almost doubled and Q 10 halved in the transplanted mesocosms in combination with an increase in activity of soil enzymes. Spectroscopic characterization of peat chemistry in the transplanted mesocosms confirmed the deepening of soil oxygenation which, in turn, stimulated microbial decomposition. After 3 years, soil carbon stock increased only in the control mesocosms whereas a reduction in mean annual carbon accumulation of c. 30% was observed in the transplanted mesocosms. Based on the above information, a structural equation model was built to provide a mechanistic understanding of the causal connections between peat moisture, vegetation response, soil respiration and carbon accumulation. This study identifies, in the feedback between plant and microbial responses, the primary pathways explaining the reduction in carbon accumulation in response to recurring climate extremes in peat soils.

Effects of an extended drought period on physiological properties of grassland species in the field - Constant Signarbieux; Urs Feller (Journal of Plant Research, 2012)

Genotypic variation in drought stress response and subsequent recovery of wheat (Triticum aestivum L.) - Valya Vassileva; Constant Signarbieux; Iwona Anders; Urs Feller (Journal of Plant Research, 2011)